2006
DOI: 10.1111/j.1746-6342.2006.00037.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of gastro‐oesophageal flap valve is useful for diagnosing gastro‐oesophageal reflux disease

Abstract: Summary Background Gastro‐oesophageal flap valve (GEFV) grade correlated with endoscopic reflux oesophagitis (RE) prevalence. Aim To investigate relationships among gastro‐oesophageal reflux disease (GERD) symptoms, RE and/or non‐erosive reflux disease (NERD) and GEFV grades in subjects undergoing endoscopy. Methods We enrolled 1305 subjects from whom endoscopic results and the results of a self‐administered questionnaire (QUEST) were available. Subjects were evaluated for GERD symptoms (QUEST score), GEFV gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…There were very few Asian data about the prevalence of abnormal GEFV. Iwamoto et al 7 reported that the prevalence of abnormal GEFV in Japan was 13.5% with a total GERD prevalence of 27.0% among patients undergoing endoscopic examination. In another study in Taiwan, Lin et al 6 reported that the prevalence of ab-normal GEFV was 27.3% with a total GERD prevalence of 41.3% among subjects undergoing routine check-ups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There were very few Asian data about the prevalence of abnormal GEFV. Iwamoto et al 7 reported that the prevalence of abnormal GEFV in Japan was 13.5% with a total GERD prevalence of 27.0% among patients undergoing endoscopic examination. In another study in Taiwan, Lin et al 6 reported that the prevalence of ab-normal GEFV was 27.3% with a total GERD prevalence of 41.3% among subjects undergoing routine check-ups.…”
Section: Discussionmentioning
confidence: 99%
“…The association between GEFV and gastroesophageal reflux disease (GERD) has been already reported in several previous studies. [2][3][4][5][6][7] However, most of these studies were conducted on patients with reflux esophagitis (RE) [2][3][4][5] and there were very few studies on patients with dyspepsia and non-erosive reflux disease (NERD). 6,7 There have been no studies investigating the distribution of abnormal GEFV among patients with dyspepsia, NERD and different grades of RE in the same set of patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GEFV grading system defines anatomical distortions that are milder than obvious HH 4 . Validation studies of this grading system have shown that abnormal GEFV findings are associated with the presence of GERD symptoms, 6 the presence of abnormal acid exposure, 38,39 the degree of exercise‐induced reflux, 4 the presence and severity of EE, 5,6,38–42 and the risk of newly developing EE after Helicobacter pylori eradication 5,43 . Three of these studies have also shown an association between abnormal GEFV findings and the prevalence of BE, 38–40 but biopsy confirmation of BE was done in only one of these studies 39 …”
Section: Discussionmentioning
confidence: 99%
“… 3 is used as an endoscopic descriptor of anatomical integrity of the EGJ. Although this grading system parameterizes aberrations that are more subtle than obvious hiatal hernia (HH), HH is frequently detected in patients with grade 3 flap valves as well as in patients with grade 4 flap valves, HH being always present in the latter group 4–6 . Hill's grading system not only involves a description of the musculo‐mucosal fold, but it also grades the stepwise relaxation of the EGJ 3,4 .…”
Section: Introductionmentioning
confidence: 99%